Assessing the Efficacy of a Bacteriophage Cocktail, Comprised of Three Monophages, Against Campylobacter spp. in Broiler Chickens - Cole, Annalie (2025)
Campylobacter species are the leading cause of foodborne illness across the globe, with chicken meat being the main source of infection. The development of resistance, by campylobacters, to key antibiotics limits the treatment options for consumers, heightening the need to prevent transmission to humans in the first instance. This study was conducted to assess the efficacy of a bacteriophage cocktail, named CampyShield, in reducing Campylobacter counts in the caeca and liver of broiler chickens. The efficacy of CampyShield in Campylobacter reduction was compared with that of CP30A (a commonly used Campylobacter bacteriophage). Firstly, 160 trial birds were allocated to treatment groups, as described in section 2.6., and were infected with CampyShield, CP30A and Campylobacter to assess the extent of Campylobacter reduction in the caeca. Campylobacter phage-resistant isolates from the birds, were then detected, post-trial, and subjected to various resistance tests such as sensitivity testing to the CampyShield cocktail phages and CP30A, motility testing and carrier state testing. Phage-resistant isolates were also sequenced to identify phase variation, conferring resistance mechanisms. The detection of CampyShield and the presence of Campylobacter in the liver of trial birds was then discussed, to assess whether there was translocation by either entity from the caeca of the broiler chickens into the liver and to assess the efficacy of CampyShield in the liver. Lastly, in vitro investigations were carried out on the CampyShield constituent phages against Campylobacter strains to further determine the efficacy of the cocktail. These investigations included measuring host strain diversity, calculating efficiency of plating (EOP) values against certain strains and measuring the extent of resistance to the CampyShield constituent phages, by C. jejuni NCTC 12662, after 24 h. DNA sequences of these resistant strains were also obtained, to identify resistance mechanisms through phase variation.